2019
DOI: 10.1126/sciadv.aaw0480
|View full text |Cite
|
Sign up to set email alerts
|

Bcl11b prevents fatal autoimmunity by promoting T reg cell program and constraining innate lineages in T reg cells

Abstract: Regulatory T (Treg) cells are essential for peripheral tolerance and rely on the transcription factor (TF) Foxp3 for their generation and function. Several other TFs are critical for the Treg cell program. We found that mice deficient in Bcl11b TF solely in Treg cells developed fatal autoimmunity, and Bcl11b-deficient Treg cells had severely altered function. Bcl11b KO Treg cells showed decreased functional marker levels in homeostatic conditions, inflammation, and tumors. Bcl11b controlled expression of essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 42 publications
4
42
0
Order By: Relevance
“…Loss of FoxP3 (even slight reductions) often results in generation of exTregs [ 29 , 30 ], while conversion into Teff with unaltered FoxP3 expression is called Treg “fragility” [ 31 ]. Several factors appear to be important for Treg stability/fragility, including IL-2/STAT5 signals [ 11 , 28 , 32 ], Pten/Akt/Foxo1/3a pathway [ 33 , 34 ], autophagy [ 35 ], CARMA1–BCL10–MALT1 (CBM) signalosome complex [ 36 ], Ezh2 [ 37 ], Bcl11b [ 38 ], Eos [ 39 ], PP2A [ 40 ], and Nrp1 [ 31 ]. While the former six pathways are required to stabilize FoxP3, ablation of the latter three factors does not affect FoxP3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of FoxP3 (even slight reductions) often results in generation of exTregs [ 29 , 30 ], while conversion into Teff with unaltered FoxP3 expression is called Treg “fragility” [ 31 ]. Several factors appear to be important for Treg stability/fragility, including IL-2/STAT5 signals [ 11 , 28 , 32 ], Pten/Akt/Foxo1/3a pathway [ 33 , 34 ], autophagy [ 35 ], CARMA1–BCL10–MALT1 (CBM) signalosome complex [ 36 ], Ezh2 [ 37 ], Bcl11b [ 38 ], Eos [ 39 ], PP2A [ 40 ], and Nrp1 [ 31 ]. While the former six pathways are required to stabilize FoxP3, ablation of the latter three factors does not affect FoxP3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Upon disruption of CBM, the majority of TI-Tregs produce IFN-γ, followed by stunted tumour growth [ 70 ]. Treg-specific deletion of Bcl11b showed decreased functional marker levels under homeostatic conditions, during inflammation, and in tumours [ 134 ]. Additionally, genome-wide occupancy studies coupled with gene expression profiling revealed that Bcl11b, in association with Foxp3, is critical for establishing a Treg-specific gene activation programme.…”
Section: New Function and Regulatory Mechanisms For Tregsmentioning
confidence: 99%
“…Its role in the formation of specific T-cell subsets at different stages of T-cell development and maturation was further investigated. Bcl11b was shown to be required for the development of γδ T-cells ( Shibata et al, 2014 ; Hatano et al, 2017 ; Dolens et al, 2020 ), iNKT cells and T-regulatory cells ( Albu et al, 2011 ; Vanvalkenburgh et al, 2011 ; Uddin et al, 2016 ; Drashansky et al, 2019 ; Hasan et al, 2019 ). Additionally, Bcl11b is involved in the differentiation of CD4 + CD8- helper T cells and CD4-CD8 + cytotoxic T cells through the regulation of key transcription factors ThPOK and Runx3 ( Kojo et al, 2017 , 2018 ).…”
Section: General Features Of Ctip2/bcl11bmentioning
confidence: 99%
“…Studies on the role of Bcl11b in Treg cells of both humans and mice identified more than 500 targets for Bcl11b. Interestingly, the top 2 enriched motifs for Bcl11b binding were Ets and Runx binding motifs ( Drashansky et al, 2019 ; Hasan et al, 2019 ). Similarly, more than 900 and 94 Bcl11b targets were observed in pro-T cells and ILC2 cells, respectively ( Hosokawa et al, 2020 ).…”
Section: General Features Of Ctip2/bcl11bmentioning
confidence: 99%
See 1 more Smart Citation